The long-run relationship between outward FDI and total factor productivity: Evidence for developing countries - Dierk Herzer (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2010)
This paper examines the long-run relationship between outward foreign direct investment (FDI) and total factor productivity for a sample of 33 developing countries over the period 1980-2005. Using panel cointegration techniques, we find that: (i) outward FDI has, on average, a positive long-run effect on total factor productivity in developing countries, (ii) increased factor productivity is both consequence and a cause of increased outward FDI, and (iii) there are large differences in the long-run effects of outward FDI on total factor productivity across countries. Cross-sectional regressions indicate that these cross-country differences in the productivity effects of outward FDI are significantly negatively related to cross-country differences in labor market regulation, whereas there is no statistically significant association between the productivity effects of outward FDI and the level of human capital, the level of financial development, or the degree of trade openness in the home country.
Keywords: F21; O11; F23; C23; 330; outward FDI; total factor productivity; developing countries; panel cointegration; Direktinvestition; Produktivität; Kointegration; Panel; Entwicklungsländer